Comparison of Protein Acetyltransferase Action of CRTAase with the Prototypes of HAT - Prija Ponnan; Ajit Kumar; Prabhjot Singh; Prachi Gupta; Rini Joshi; Marco Gaspari; Luciano Saso; Ashok K. Prasad; Ramesh C. Rastogi; Virinder S. Parmar; Hanumantharao G. Raj (The Scientific World Journal)
Our laboratory is credited for the discovery of enzymatic acetylation of protein, a phenomenon unknown till we identified an enzyme termed acetoxy drug: protein transacetylase (TAase), catalyzing the transfer of acetyl group from polyphenolic acetates to receptor proteins (RP). Later, TAase was identified as calreticulin (CR), an endoplasmic reticulum luminal protein. CR was termed calreticulin transacetylase (CRTAase). Our persistent study revealed that CR like other families of histone acetyltransferases (HATs) such as p300, Rtt109, PCAF, and ESA1, undergoes autoacetylation. The autoacetylated CR was characterized as a stable intermediate in CRTAase catalyzed protein acetylation, and similar was the case with ESA1. The autoacetylation of CR like that of HATs was found to enhance protein-protein interaction. CR like HAT-1, CBP, and p300 mediated the acylation of RP utilizing acetyl CoA and propionyl CoA as the substrates. The similarities between CRTAase and HATs in mediating protein acylation are highlighted in this review.